Inspirerx24 integrating newcomers for success and personal initiative in resilient engage - Rosly, Nur Arnida; Zamer, Muhammad ‘Izzuddin; Ibrahim, Norkasihan (2025)
The Faculty of Pharmacy came alive on October 12 , 2025, as INSPIRERX24 took place at Examination Hall 1 and various locations around the faculty, with a total of 239 participants. Organised by the Society of Pharmacy Students (SOPHYS) and the Faculty of Pharmacy Student Secretariat (SMF), this year’s theme, “Squid Game,” served as a platform to welcome new students while fostering teamwork and engagement. th The morning session began with a sharing session by the Deputy Dean of Student Affairs, followed by insightful talks from the alumni, faculty counselor, and assistant registrar. Participants were also introduced to the Faculty of Pharmacy’s Student Representative Council and Sekreteriat Majlis Perwakilan Pelajar (SMPP) representatives, as well as the various student societies within the faculty.